COMPARISON OF CARPASTRETCH® WITH SPLINT IN NON-SURGICAL TREATMENT OF CARPAL TUNNEL SYNDROME: A RANDOMIZED OPEN LABEL STUDY - Malshikare, Vijay; Desai, Sanjay Mukund; Arekar, Anil Shridhar; Bhosale, Neelambari Abhay; Bonde, Shital Ravindra; Awdhani, Mansi Abhishek (Malang Neurology Journal, 2019)
Background: The present study was conducted with an aim to compare the efficacy and safety of CarpaStretch® relative to wrist splinting in patients with CTS.Objective: To examine the effect of using CarpaStretch®, a novel dynamic splint for the treatment of Carpal Tunnel Syndrome.Methods: The efficacy and safety of CarpaStretch® was compared with conventional splints in a prospective 6-month trial with a follow-up at 12 months. 30 subjects with confirmed Carpal Tunnel Syndrome were enrolled in each group. Nerve conduction tests, wrist MRI, provocation tests and patient satisfaction questionnaires were assessed in the study.Results: At the end of 6 months, there were significant increases in sensory nerve conduction velocity in both intervention and control groups, and the difference between groups were not significant. A higher proportion of subjects using CarpaStretch® showed improvement in severity grade relative to control at 6 months. Small but clinically meaningful increases were seen in carpal tunnel dimensions in the CarpaStretch® group. There was a greater reduction in the incidence of paraesthesia and increase in the time of paraesthesia in the CarpaStretch® group. No adverse effects were reported in either group, but 4 subjects in the control group opted for surgery.Conclusion: CarpaStretch® can be used for effective non-surgical management of Carpal Tunnel Syndrome.